الانتقاء في كرة القدم - مزروع, السعيد; زروال, محمد (Sciences de l'Homme et de la Société; Vol. 19 (2016): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ)
يهدف هذا الموضوع إلى التعرف على عملية الانتقاء في المجال الرياضي بصفة عامة وفي الألعاب الجماعية وكرة القدم بصفة خاصة هذا من جهة، من جهة أخرى توضيح مختلف أنواع الانتقاء ومراحله، إضافة إلى ذلك التطرق إلى أبرز الطرق للاختيار أو الانتقاء بكرة القدم.     Abstract : The objective of this study seeks to identify; on one hand, the process of selection within the field of sports in general and football in particular. On the other hand, it illustrates the different types of selection and its steps. Additionally, to know the most important means and methods for the selection in football.